Effect of Freeze-Drying of Pre-Processed Broccoli on Drying Kinetics and Sulforaphane Content [Efecto de la Liofilización de Brócoli Pre-Procesado Sobre la Cinética de Secado y el Contenido de Sulforafano] - Reyes-Salinas, A; Mahn-Osses, A; Roman-Aliste, J (Centro de Informacion Tecnologica, 2016)
Freezer-drying of pre-processed broccoli blocks were studied through a 31?21 factorial design to investigate the effect of the broccoli blocks thickness (5 mm; 7.5 mm; 10 mm) and freezing rate (high: immersion in liquid nitrogen; low: household freezer) on drying kinetics, sulforaphane and moisture content. The maximum sulforaphane content was achieved with 7.5 mm thickness and high freezing rate. In this condition, sulforaphane content was increased by 29.75 % [3.057 μmol/g dry matter] compared to the situation before drying, corresponding to pre-processed broccoli (blanched and incubated) in optimal conditions [2.356 μmol/g dry matter]. According to the response surface analysis, the optimal conditions to obtain freeze-dried broccoli are 8.3 mm thickness and high freezing rate, resulting in a sulforaphane content equal to 3.02 [μmol/g dry matter]. The primary drying period was completed only for thickness of 5.0 and 7.5 mm. Adjustment of drying curves to the simplified constant diffusivity model gave effective moisture diffusivity values between 7.4·10-11 and 1.23·10-10 [m2/s]. The drying curves were adjusted with three empirical models (Page, Weibull y Logarithmic). The best fittings were obtained with the Page and the Logarithmic models (R2 ≥0.995).